Kepastian Hukum Dalam Penyelesaian Sengketa Pelanggaran Perjanjian Lisan Yang Berpotensi Terjadi Pelanggaran Hukum (RechtJiva, 2025)
This study discusses legal certainty in the settlement of disputes arising from breaches of verbal agreements that have the potential to cause legal violations from the perspective of Indonesian civil law. Verbal agreements are still commonly found in society, especially in social relationships and economic activities based on the principle of trust. However, agreements that are not set out in writing often give rise to legal problems when there is a breach or default that is detrimental to one of the parties. The purpose of this study is to analyze the legal position of verbal agreements, examine the legal consequences if the agreement is violated, and identify forms of legal protection for parties acting in good faith. This study uses a normative juridical method with a legislative approach and case analysis, as well as examining secondary data in the form of legal literature, court decisions, and provisions of the Civil Code (KUHPerdata). The results of the study show that although verbal agreements meet the requirements for a valid agreement as stipulated in Article 1320 of the Civil Code, violations often cause legal uncertainty due to weak evidence and the difficulty of proving the intentions of the parties. Therefore, it is necessary to strengthen public awareness of the importance of written agreements and to update the mechanism of evidence to ensure legal protection and achieve justice in the settlement of verbal agreement disputes.